Role of minimally invasive secondary cytoreduction in patients with recurrent ovarian cancer. Issue 2 (13th January 2023) - Conte, Carmine; Marchetti, Claudia; Loverro, Matteo; Giudice, Maria Teresa; Rosati, Andrea; Gallotta, Valerio; Scambia, Giovanni; Fagotti, Anna
Abstract : Objective: Retrospective series have shown minimally invasive secondary cytoreductive surgery is a feasible approach in selected cases of recurrent ovarian cancer. However, no predictors of minimally invasive secondary cytoreductive surgery feasibility are currently available. This study aims to identify predictive factors of minimally invasive secondary cytoreductive surgery feasibility and to compare perioperative and survival outcomes in a matched series of recurrent ovarian cancer patients who underwent secondary cytoreduction via an open or minimally invasive surgical approach. Methods: We retrospectively identified all platinum-sensitive recurrent epithelial ovarian cancer patients who underwent minimally invasive or laparotomic secondary cytoreductive surgery between January 2013 and July 2020. Each patient underwent a preoperative positron emission tomography (PET) computerized tomography (CT) scan and diagnostic laparoscopy before secondary cytoreductive surgery. A 1:2 propensity score-matched analysis was performed to balance predictive factors of minimally invasive secondary cytoreductive surgery. Results: Overall, 276 patients were identified (62 minimally invasive and 214 open), and a complete gross resection was achieved in 262 (94.9%) patients. At multivariate analysis, predictive factors for minimally invasive secondary cytoreductive surgery were neoadjuvant chemotherapy at first diagnosis (p=0.007), site of recurrence (p=0.031), and number of lesions (p=0.001). In the 1:2 propensity-matched population (39 minimally invasive and 78 open), complete gross resection was similar for both groups (p=0.082). Early post-operative complications were significantly higher in the laparotomy (33.3%) than in the minimally invasive surgery (10.3%) group (p=0.004). Only one (2.6%) patient experienced a grade >3 early post-operative complication in the minimally invasive surgery group compared with 13 (16.7%) patients in the open cohort (p<0.001). The median follow-up period was 32 months (range: 1–92) in the propensity-matched population. The median post-recurrence survival was 81 months in the minimally invasive surgery group and was not reached in the open group (p=0.11). Conclusions: Patients with single or oligometastatic recurrences can be offered minimally invasive secondary cytoreductive surgery, mainly if localized in the lymph-nodes, and/or if they received neoadjuvant chemotherapy at primary diagnosis. Minimally invasive secondary cytoreductive surgery is associated with favorable perioperative outcomes with no differences in terms of post-recurrence survival with respect to open approach.